α) α^2+2α*1/α+1/α^2-α^2+2α*1/α-1/α^2= 2+2=4β)1) ΑΝ α = 1000 ΤΟΤΕ ΕΧΟΥΜΕ (1000+1/1000)^2-(1000-1/1000)^2=4 ΣΥΜΦΩΝΑ ΜΕ ΤΗΝ ΣΧΕΣΗ ΠΟΥ ΑΠΟΔΕΙΞΑΜΕ 2) Α=(1+1/1)^2+(2+1/2)^2+....+(9+1/9)^2+(10+1/10)^2 Β=(1-1/1)^2+(2-1/2)^2+.........+(9-9/10)^2 Α-Β= 4+4+4+4+4+4+4+4+4+(1+1/10)^2 =36+(1+1/10)^2ΒΑΙΟΣ
α) α^2+2α*1/α+1/α^2-α^2+2α*1/α-1/α^2= 2+2=4
ΑπάντησηΔιαγραφήβ)
1) ΑΝ α = 1000 ΤΟΤΕ ΕΧΟΥΜΕ
(1000+1/1000)^2-(1000-1/1000)^2=4 ΣΥΜΦΩΝΑ ΜΕ ΤΗΝ ΣΧΕΣΗ ΠΟΥ ΑΠΟΔΕΙΞΑΜΕ
2) Α=(1+1/1)^2+(2+1/2)^2+....+(9+1/9)^2+(10+1/10)^2
Β=(1-1/1)^2+(2-1/2)^2+.........+(9-9/10)^2
Α-Β= 4+4+4+4+4+4+4+4+4+(1+1/10)^2 =36+(1+1/10)^2
ΒΑΙΟΣ